Good morning and good night : poems - Wagoner, David (Illinois poetry series., 2005)
By continually discovering what's new in each day without forgetting yesterday's surprises, David Wagoner has succeeded in constantly expanding his range in a career that spans more than fifty years. In Good Morning and Good Night, this range includes his usual rich forays into nature and personalities, and poetry for all ages, young and old, amidst a vivid array of memories and explorations. Readers will find homages to the poets that have inspired him, as well as the bountiful lyricism that has made Wagoner's poetry one of our most enduring sources of delight and joy._x000B_Good Morning and Good Night features poems previously published in American Poetry Review, The American Scholar, Atlantic Monthly, Hudson Review, The Kenyon Review, New Letters, The New Republic, Poetry, Shenandoah, Southern Review, The Yale Review, and other leading literary journals._x000B__x000B_